Electrochemical growth of MNO2 into hierarchical spheres for electrochemical determination of neutrophil gelatinase-associated lipocalin for acute kidney injury. - Lin, Xi. (2012)
Using novel three-dimensional hierarchical spheres structure of MnO2 (MnO2 HS) as materials, an electrochemical immunosensor with the chemical immobilization of rabbit polygonal lipocalin-2 (LA2) antibody on MnO2 HS-modified glassy carbon electrode (GCE) is developed for neutrophil gelatinase-associated lipocalin (NGAL) detection without any label needed. The material was directly grown on the electrode using template-free electrochemical deposition under moderate conditions. The linear response range of the immunosensor is considerably wide (1ng/mL - 10μg/mL). The immunosensor achieved a low detection limit of 1ng/mL and also the potentiality to be used in the detection of NGAL in patient serum.